Core temperatures during major abdominal surgery in patients warmed with new circulating-water garment, forced-air warming, or carbon-fiber resistive-heating system - Hasegawa, Kenji (Springer Japan, 2011)
PURPOSE: It has been reported that recently developed circulating-water garments transfer more heat than a forced-air warming system. The authors evaluated the hypothesis that circulating-water leg wraps combined with a water mattress better maintain intraoperative core temperature ≥36°C than either forced-air warming or carbon-fiber resistive heating during major abdominal surgery. METHODS: Thirty-six patients undergoing open abdominal surgery were randomly assigned to warming with: (1) circulating-water leg wraps combined with a full-length circulating-water mattress set at 42°C, (2) a lower-body forced-air cover set on high (≈43°C), and (3) a carbon-fiber resistive-heating cover set at 42°C. Patients were anesthetized with general anesthesia combined with continuous epidural analgesia. The primary outcome was intraoperative tympanic-membrane temperature ≥36°C. RESULTS: In the 2 h after anesthesia induction, core temperature decreased 1.0 ± 0.5°C in the forced-air group, 0.9 ± 0.2°C in the carbon-fiber group, and 0.4 ± 0.4°C in the circulating-water leg wraps and mattress group (P < 0.05 vs. forced-air and carbon-fiber heating). At the end of surgery, core temperature was 0.2 ± 0.7°C above preoperative values in the circulating-water group but remained 0.6 ± 0.9°C less in the forced-air and 0.6 ± 0.4°C less in the carbon-fiber groups (P < 0.05 vs. carbon fiber). CONCLUSIONS: The combination of circulating-water leg wraps and a mattress better maintain intraoperative core temperature than did forced-air and carbon-fiber warming systems.